2018
DOI: 10.1093/nar/gky044
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific DNA binding activity of the cross-brace zinc finger motif of the piggyBac transposase

Abstract: The piggyBac transposase (PB) is distinguished by its activity and utility in genome engineering, especially in humans where it has highly promising therapeutic potential. Little is known, however, about the structure–function relationships of the different domains of PB. Here, we demonstrate in vitro and in vivo that its C-terminal Cysteine-Rich Domain (CRD) is essential for DNA breakage, joining and transposition and that it binds to specific DNA sequences in the left and right transposon ends, and to an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 73 publications
4
53
3
Order By: Relevance
“…3b). At the level of the CRD monomer, the observed mode of DNA binding is broadly consistent with the model derived from NMR including the identification of Y558, R567, and K569 as crucial residues for specific recognition 43 , but the NMR model did not predict the severe DNA bend induced by CRD dimerization.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…3b). At the level of the CRD monomer, the observed mode of DNA binding is broadly consistent with the model derived from NMR including the identification of Y558, R567, and K569 as crucial residues for specific recognition 43 , but the NMR model did not predict the severe DNA bend induced by CRD dimerization.…”
Section: Resultssupporting
confidence: 73%
“…4). The CRD monomers refined against the cryo-EM maps are consistent with the cross-brace Zn finger structure determined by NMR 43 , although not identical due to side chain rearrangements at the hydrophobic CRD dimer interface (Fig. 3c).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Biochemical and structural studies of DD(D/E) transposases and retroviral integrases bound to their cognate DNA substrates have revealed that assembly of a productive transpososome often involves more transposase subunits than those actually engaged in catalysis, the supernumerary subunits playing an architectural role within the transposition complex ( Montaño et al, 2012 ; Hickman et al, 2014 ); reviewed in Hickman and Dyda, 2015 ). In particular, recent studies have shown that the T. ni PB transposase dimerizes in solution ( Jin et al, 2017 ) and higher-order complexes were proposed to assemble during piggyBac transposition ( Morellet et al, 2018 ). Within a transpososome, all transposase subunits are generally identical because they are encoded by a single gene carried by the mobile element itself.…”
Section: Discussionmentioning
confidence: 99%